THE USE OF SEMANTIC MAPPING TECHNIQUE IN TEACHING READING RECOUNT TEXT - Tuti Maslahah Zahro; Etika Rachmawati (Journal of English Education Program (JEEP), 2021)
This study deals with the investigation of semantic mapping technique in teaching reading recount text.  It was intended to find out the teacher’s way in using semantic mapping technique in teaching reading recount text; and students’ perceptions toward the implementation of semantic mapping technique in teaching reading recount text.  In addition, the writer used the theory from Schmitt (2002, p. 44) who explained about teacher’s ways in implementing semantic mapping word technique in teaching reading comprehension. The writer used qualitative research with the type of case study involving an English teachers and the students of eighth grade. To collect the data, classroom observation, interview, and questionnaire were utilized.  The findings indicated that the teacher implemented the steps in conducting semantic mapping strategy as suggested by Schmitt (2002, p. 44. In addition, the students also enjoy the teaching learning process using the technique of semantic mapping. Furthermore, the major conclusion of this study indicated that the teacher was able to apply the semantic mapping technique that encourages the students to develop their reading skill.  Regarding the weakness of this research, the present study did not point out specific factors influencing students’ motivation in learning Semantic mapping. Thus, it is recommended that further researchers should investigate teacher’s perception on implementing the technique of semantic mapping  in the teaching-learning process. Keywords: reading comprehension, recount text, semantic mapping.